Comprehensive Management of a Patient with Drug Induced Gingival Overgrowth and Metabolic Syndrome - B M C A Bandaranayake; A Tilakaratne (Journal of Multidisciplinary Dental Research)
Periodontitis and metabolic syndrome demonstrate a bidirectional relationship complicated by multiple risk factors. Gingival overgrowth (GO) is a manifestation of exaggerated inflammatory response of the gingivae in response to biofilm and varying local and systemic risk factors which include medications such as antihypertentive medication- nifedipine. A patient with multiple dental care needs with GO, complicated by systemic risk factors would invariably benefit from multidisciplinary approach for care. A 57-year-old female was diagnosed with chronic periodontitis, nifedipine-induced GO and metabolic syndrome. Management encompassed initial nonsurgical periodontal therapy, where the patient was educated and guided towards better plaque control, following which, scaling, root debridement, and surgical therapy (gingivectomy and excisional new attachment procedure) were carried out. Along with periodontal therapy, she was also managed through restorative phase where a successful outcome was achieved. She was then followed-up with maintenance care, and nifedipine was substituted with captopril by the Physician to facilitate maintenance. Keywords: Metabolic syndrome, Gingivectomy, Drug-induced gingival overgrowth, Periodontitis, Excisional new attachment procedure